Mapping processing strategies in learning from expository text: an exploratory eye tracking study followed by a cued recall - Catrysse, Leen; Gijbels, David; Donche, Vincent; De Maeyer, Sven; Van den Bossche, Piet; Gommers, Luci (Frontline Learning Research, 2016)
This study starts from the observation that current empirical research on students’ processing strategies in higher education has mainly focused on the use of self-report instruments to measure students’ general preferences towards processing strategies. In contrast, there is a rather limited use of more direct and online observation techniques to uncover differences in processing strategies at a task specific level. We based our study on one of the most influential studies in the domain of Students’ Approaches to Learning (SAL) (Marton, Dahlgren, Säljö, & Svensson, 1975). In our exploratory experiment we used eye tracking followed by a cued recall to investigate how students use processing strategies in learning from expository text. Nineteen university students participated in the experiment. Results suggested that students in the deep condition did not look longer at the essentials in the text compared with students in the surface condition, but that they processed them in a more deep way. In our sample, students in the surface condition looked longer at facts and details and also reported repeating these facts and details more often. We suggest that the combination of eye tracking followed by a cued recall is a promising tool to investigate students’ processing strategies since not all differences in processing strategies are reflected in overt eye movement behaviour. The current methodology allows researchers in the domain of SAL to complement and extend the present knowledge base that has accumulated through years of research with self-report questionnaires and interviews on students’ general preferences towards processing strategies.